A collaborative architecture of the industrial internet platform for manufacturing systems. (February 2020) - Wang, Junliang; Xu, Chuqiao; Zhang, Jie; Bao, Jingsong; Zhong, Ray
Highlight: A collaborative architecture of the industrial internet platform for manufacturing systems. An industrial driver is presented to realize the ``plug and play" to the industrial internet platform. The digital thread is designed to link all resource units and meta-data, which consists of a digital resource chain and an integrated information chain. All the businesses in the enterprise information systems are decoupled into different micro-services, and a "Jigsaw Apps" can be recombined to support the operation of manufacturing systems. A case study is conducted to illustrate the effectiveness of the proposed Ind-OS, and the impact caused by the Ind-OS are discussed. Abstract: One of the most significant advances in the development of intelligent manufacturing is represented by the industrial Internet, which is combining the physical and cyber components in manufacturing systems together. Aiming to manage the interaction between the physical and cyber components, this paper proposes a collaborative architecture for industrial Internet platform (IIP) called industrial operation system (Ind-OS), which contains the industrial driver, digital thread and micro-services to provide a better cooperative enterprise information system (EIS) environment for manufacturing systems. The industrial driver in the edge layer is presented for each resource unit for communication, computation, control, identification, insight and interoperation, realizing a ``plug and play" fashion in IIP. The digital thread is designed to link all resource units and meta-data, which consists of a digital resource chain and an integrated information chain. In the application layer, all the businesses in EIS are decoupled into different micro-services, and a "Jigsaw Apps" is recombined to support the operation of manufacturing systems. A case study illustrates the effectiveness of the proposed Ind-OS, and the impacts caused by the Ind-OS are discussed.